OPTIMIZATION OF SLOTTED JACK SEPARATION FORCE BASED ON FINITE ELEMENT SIMULATION AND TAGUCHI METHOD - LIANG YunZhong; LI Hong; XU WeiPeng (Jixie qiangdu)
In order to solve the present situation of big dispersion degree of the slotted jack contact separation force,Finite element simulation and Taguchi method is proposed to optimize the range and the dispersion degree of the separation force. The structural parameters that affect the separation force of the slotted jack were analyzed,the separation force of the slotted slot in different groove depth（ h）,slot width（ d） and interference amount（ δ） was calculated by the finite element simulation model,The simulation data were analyzed by Taguchi method,The results show that the combination of the parameters is h = 3. 7 mm,d= 0. 3 mm,δ = 0. 05 mm has the strongest anti-interference ability when the separation force range is 0. 3 N 0. 8 N. The separation force test was carried out before and after the size optimization,The results show that the separation force of the jack is from 0. 524 N to 0. 539 N,and the standard deviation becomes from 0. 094 to 0. 078. The optimization of the separation force of the slotted jack based on finite element simulation and Taguchi method provides a reference for the optimal design of the contact.